Gambaran Pengelolaan (Hutan Kemasyarakatan) HKm di Indonesia - Muhdar, Muhdar; Dirawan, Gufron D; Wiharto, Muhammad (UNM Environmental Journals, 2018)
This study aims: To describe the management of Community Forestry (HKm) in Indonesia. Through a theoretical study of some of the results of research on community forest management in Indonesia. Then the results of this study show that the management of HKm is more oriented to short-term economic interests, not ecologically and economically sustainable, resulting in damage to forest functions, both ecological and economic functions, due to various problems faced by the field and inequality between government regulations. The solution to the results of this study is that in the management of Community Forestry, it is necessary to pay attention to three principles, namely: a) Benefit and are ecologically, economically, socially and culturally sustainable, b). deliberation; and justice for the whole community.